Android-Based Application of Dispensation Licensing System for Urban Freight Transport in Surakarta City - Budi Yulianto; Setiono; Nurul Hidayati; Salsabila Naura Putri (Universitas Muhammadiyah Surakarta, 2026)
Urban freight transport poses significant challenges to traffic management, road safety, and environmental sustainability in Surakarta City. This study examines the development and implementation of the SIMABA application, operationalized as the SIDJAKA digital dispensation licensing system, for monitoring and controlling urban freight transport movements. The freight transport trip characteristic survey was conducted to identify origin-destination trips, frequency, weight and type of cargo, and distribution patterns. The road inventory survey was intended to obtain road geometry data, while the traffic count survey was done to collect traffic volume during peak hours. Meanwhile, secondary data consisting of information on road functions and bearing capacity, land use of activity centers, traffic signs, and administrative licenses submitted through SIDJAKA application from January 2020 to December 2025 were obtained from relevant institutions. This study demonstrates that the SIMABA application, implemented through the SIDJAKA system, effectively regulates the licensing of freight transport in Surakarta City. Monitoring of this application can be carried out systematically and transparently, ensuring that administrative and technical requirements, particularly vehicle roadworthiness, are met, thus ensuring more controlled urban freight transport. The analysis of origin-destination trips indicates that freight transport flows are significantly influenced by changes in the road network and infrastructure development, with the distribution activities remaining concentrated in market areas and major commercial corridors. Although effective, the system faces limitations in terms of cross-regional scale, data integration, maintenance systems, and digital user literacy, which may hinder its adoption and optimal utilization. As a future research agenda, developing the system into an integrated platform that connects cross-regional licensing, vehicle inspection systems, and electronic law enforcement is recommended to achieve greater adaptability and efficiency.